Disseminated Mucormycosis in Patient with Acute Lymphoblastic Leukemia (Clinical Case) - S. N. Khostelidi; A. P. Shapochnik; Yu. V. Monina; S. B. Zaycev; T. S. Bogomolova; N. N. Klimko (Журнал инфектологии)
.